Hubungan Dukungan Keluarga dan Efikasi Diri dengan Kepatuhan Minum Obat Anti Tuberkulosis (OAT) pada Pasien TB Paru di Puskesmas Kabupaten Situbondo - Rahman, Handono Fatkhur; Widad, Sofil; Sholehah, Baitus (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, primarily affecting the lungs and leading to significant health challenges. In 2021, 450,000 cases of multidrug-resistant tuberculosis (MDR-TB) were reported, marking a 3.1% increase from the previous year. Family support plays a vital role in motivating patients to adhere to treatment regimens, while high self-efficacy boosts patients' confidence in completing therapy. Adherence to tuberculosis treatment is defined as completing a six-month course of therapy without interruptions. This study aimed to analyze the relationship between family support, self-efficacy, and adherence to anti-tuberculosis medication (OAT) among pulmonary TB patients in Situbondo District. A cross-sectional design was employed, involving 112 respondents selected through Slovin's formula from a population of 156 TB patients at Besuki and Panji Health Centers. Data collection utilized validated questionnaires on family support, self-efficacy, and medication adherence, analyzed using the Spearman test. Results revealed a significant relationship between family support and adherence (p=0.000; r=0.443) and between self-efficacy and adherence (p=0.000; r=0.537). The study concludes that both family support and self-efficacy are crucial factors influencing adherence to tuberculosis treatment among pulmonary TB patients in Situbondo.